Stochastic approximation-solvability of linear random equations involving numerical ranges. (1997) - Verma, Ram U.
Abstract : The random (or stochastic) approximation-solvability, based on a projection scheme, of linear random operator equations involving the theory of the numerical range of a bounded linear random operator is considered. The obtained results generalize results with regard to the deterministic approximation-solvability of linear operator equations using the Galerkin convergence method.